Análisis de los costos de producción y su incidencia en la rentabilidad de las microempresas florícolas ubicadas en la parroquia Joseguango Bajo cantón Latacunga en el primer trimestre del año 2019. - Quizhpe Sarango, Digna Susana (2020)
This research work refers to the analysis of production costs and its incidence on the profitability of flower-growing micro companies located in Joseguango Bajo parish. It was identified as a problem, the lack of awareness by the producers, the data collection was carried out through the application of research techniques and instruments such as: direct observation and interview the owners of several flower-growing companies. The main objective of the investigation is to determine the incurred costs on the production of different kind of roses like: Freedom, Nena, Pink Floyd, Mondial, Vendela, and Explorer in order to know the unit cost and total cost. The process cost system is a method that is used in companies whose production is continuous, where several processes are described to obtain a finished product. On the cost calculation, fertilizers and fungicides were identified as supplies and materials; for labour, several activities which are carried out during the processes were detailed, such as: Weeding, Taking out trash, Cutting the top off, Unbudding, Pruning, Scrubbing, Scarifying, Watering, Fertilizing, Fumigating, Harvesting, and Meshing that allowed to know the real cost of the second element of the cost. On the Indirect Manufacturing Costs, the depreciations of assets held by the floriculturists were considered. The analyzed data showed an average unit cost of 0.0883 cents per stem which established that micro companies have earnings in relation to the price of sales, depending on the season. The application of profitability indicators permitted to know the current situation of flower-growing companies, where the generated average profit is 0.62 cents for every sold dollar. Finally, the cost of production affects 8.83% on the profitability of small producers, it means, a higher the cost - a lower profitability. The obtained result can be used as a guide for producers who wish to undertake the cultivation of roses.